Razões de mortalidade frente ao efeito desigualdade em estudos de mortalidade associada a categorias ocupacionais e níveis sociais Mortality ratios in the light of the Inequality Effect in studies of the mortality associated with occupational categories and social classes - Davi Rumel (Universidade de São Paulo, 1988)
As razões de mortalidade: "Standardized Risk Ratio" (SRR), "Standardized Mortality Ratio" (SMR) e "Standardized Proportional Mortality Ratio" (SPMR) são apresentadas visando divulgar uma metodologia para o estudo da mortalidade associada a categorias ocupacionais e níveis sociais. Discute-se a influência do "Healthy Worker Effect" e do Efeito Desigualdade na escolha da população de referência e apresenta-se uma forma operacional de testar a significância estatística dessas razões. The mortality ratios: the standardized risk ratio (SRR), the standardized mortality ratio (SMR), and the standardized proportional mortality ratio (SPMR) are presented with the purpose of disseminating a methodology for the study of the mortality associated with occupational categories and social classes. The influence of the "Healthy Worker Effect" and of the "Inequality Effect" in the choice of the reference population is disucussed. An operational means of testing the statistical significance of these ratio is also presented.